The development of a rapid chloride test for concrete and its use in engineering practice - Streicher, Pieter Emilius (Department of Civil Engineering, 2016)
The test is of low cost, has a sound theoretical basis, and as far as can be ascertained, is the most rapid of all chloride tests developed to date. Due to the short test duration, it is possible to test concretes cured for very short periods. Samples can also be left immersed in chloride solution and re-tested at later ages to study time-dependent phenomena such as chloride binding. The chloride conductivity test involves the standardisation of the concrete pore solution by vacuum-saturating a concrete sample with a 5 M NaCl solution. A single conductivity measurement of the sample is then performed. Different concrete samples yield different conductivities primarily because of differences in their pore and micro-structure. The measured conductivity is related to the diffusibility ratio as well as to the theoretical steady state chloride diffusivity of concrete. Trial tests were performed to determine the optimum conditions for the test (sample conditioning. test procedure) and to verify the test relationships.